دور صناديق الاستثمار الخاصة في تمويل انشاء نمو المؤسسات الناشئة - دراسة حالة الولايات المتحدة الامريكية وفرنسا - عايش شيماء; إيمان بن وارث (My University, 2022)
The study aimed to get to know the concept leadership and emerging institutions and the extent of their contribution to achieving development and advancing the economies of countries. In order for our study to be complete, we have studied private investment funds as a financing alternative and one of the financing sources that such type of institutions resort to. This study is supported by two leading international experiences in this field, namely, the United States of America and the French experience in Europe. The study concluded that entrepreneurship is an important driver of economic growth, and this is what made governments work to support emerging institutions, which are an important source of wealth, in addition to deducing that the American model is a pioneering model, along with the French, due to the contribution of these two countries in financing emerging institutions, accordingly a number of recommendations can be proposed including encouraging the creation of private investment funds offering various amenities and facilitis.encoraging innovation research and development in universities and research centers.work to the financial market which provides investors with the best exit mechanism from funded institutions. ........................................................... هدفت الدراسة إلى التعرف على مفهوم القيادة والمؤسسات الناشئة ومدى مساهمتها في تحقيق التنمية والنهوض باقتصاديات الدول. وحتى تكتمل دراستنا قمنا بدراسة صناديق الاستثمار الخاصة كبديل تمويلي وأحد مصادر التمويل التي يلجأ إليها هذا النوع من المؤسسات. وتدعم هذه الدراسة تجربتين عالميتين رائدتين في هذا المجال، وهما الولايات المتحدة الأمريكية والتجربة الفرنسية في أوروبا. وخلصت الدراسة إلى أن ريادة الأعمال محرك مهم للنمو الاقتصادي، وهذا ما جعل الحكومات تعمل على دعم المؤسسات الناشئة التي تشكل مصدرا مهما للثروة، بالإضافة إلى استنتاج أن النموذج الأمريكي يعد نموذجا رائدا إلى جانب النموذج الفرنسي. ونظراً لمساهمة هذين البلدين في تمويل المؤسسات الناشئة، وعليه يمكن اقتراح عدد من التوصيات منها تشجيع إنشاء صناديق الاستثمار الخاصة التي تقدم مختلف وسائل الراحة والتسهيلات.تشجيع الابتكار والبحث والتطوير في الجامعات ومراكز البحوث. السوق المالي الذي يوفر للمستثمرين أفضل آلية للخروج من المؤسسات الممولة